Diastolic Dysfunction of the Left and Right Ventricles in Patients with Ischemic Heart Disease at the Early Stages of Chronic Heart Failure (Eurasian Medical Research Periodical, 2025)
The concept of “diastolic dysfunction” is based on both structural and functional remodeling of cardiomyocytes and the interstitial matrix, leading to increased myocardial stiffness [2,4]. Unlike systole, during which Ca²⁺ ions are actively released from the sarcoplasmic reticulum into the cytosol, myocardial relaxation is an energy-dependent process associated with the active transport of Ca²⁺ ions back into the sarcoplasmic reticulum against a concentration gradient [10]. This mechanism explains why disturbances in myocardial relaxation occur earlier than systolic dysfunction, particularly under conditions of myocardial ischemia in ischemic heart disease (IHD) [3,6,9]. The mechanisms underlying impaired diastolic function in IHD can be conventionally divided into two categories: disorders of active relaxation caused by the development of cardiosclerosis and those associated with myocardial ischemia